Comprehensive computational fluid dynamics model of solid oxide fuel cell stacks. (7th December 2016) - Nishida, R.T.; Beale, S.B.; Pharoah, J.G.
Abstract: This paper describes the development and application of a novel computational fluid dynamics model which allows the investigation of large solid oxide fuel cell stacks in practical computation times. Comparisons with a previously verified model match quantitatively to within 3% difference for all parameters of a benchmark case and solve within 1.5% the computation time for parallel flows of air and fuel in a cell, verifying the present model as a practical option in stack design. The model is used to demonstrate that the distribution of flow rates to each cell in a 100 cell stack significantly affects the temperature distribution and overall electrochemical performance. In a further analysis, it is quantitatively demonstrated that it would be misleading to attempt to predict performance or optimise manifold designs based on a model with uncoupled transport and electrochemistry. Highlights: Detailed computational fluid dynamics models of fuel cells are not suitable for application to large stacks. The present model employs a distributed resistance analogy, and preserves all major features, at reduced computational cost. Rate terms are substituted in the core of the stack, while the full Navier Stokes equations are solved in the manifolds. Agreement of the present model with a detailed model is within 3%. The results of parametric studies on a 100-cell stack are presented and discussed.